Proteoglycan-driven Autophagy: A Nutrient-independent Mechanism to Control Intracellular Catabolism. (November 2020) - Neill, Thomas; Buraschi, Simone; Kapoor, Aastha; Iozzo, Renato V.
Proteoglycans are rapidly emerging as versatile regulators of intracellular catabolic pathways. This is predominantly achieved via the non-canonical induction of autophagy, a fundamentally and evolutionarily conserved eukaryotic pathway necessary for maintaining organismal homeostasis. Autophagy facilitated by either decorin, a small leucine-rich proteoglycan, or perlecan, a basement membrane heparan sulfate proteoglycan, proceeds independently of ambient nutrient conditions. We found that soluble decorin evokes endothelial cell autophagy and breast carcinoma cell mitophagy by directly interacting with vascular endothelial growth factor receptor 2 (VEGFR2) or the Met receptor tyrosine kinase, respectively. Endorepellin, a soluble, proteolytic fragment of perlecan, induces autophagy and endoplasmic reticulum stress within the vasculature, downstream of VEGFR2. These potent matrix-derived cues transduce key biological information via receptor binding to converge upon a newly discovered nexus of core autophagic machinery comprised of Peg3 (paternally expressed gene 3) for autophagy or mitostatin for mitophagy. Here, we give a mechanistic overview of the nutrient-independent, proteoglycan-driven programs utilized for autophagic or mitophagic progression. We propose that catabolic control of cell behavior is an underlying basis for proteoglycan versatility and may provide novel therapeutic targets for the treatment of human disease: